Son-of-God traditions in the Synoptic Gospels: Ferdinand Hahn"s diachronic perspective - Dreyer, Yolanda (HTS teologiese studies, 2001)
This study makes use of Ferdinand Hahn's insights (with Son of God as case study) to indicate how the naming of Jesus developed in stages. It is shown that the name Son of God was not used by Jesus. It functioned within the context of the cultic activities of early Christianity, was taken over from the surrounding religious, political and cultural world while its referential meaning shifted in the various layers. Hahn focuses on the multi-stage development of the Jesus tradition from an Aramaic "Judaism", through a Hellenistic "Judaism" to a Gaeco-Roman stage. First the possible historical origins of the title Son of God are discussed, after which Hahn's view is taken into consideration.